2007
DOI: 10.1161/01.str.0000254495.26827.2e
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Endothelial-Independent Vasodilation Are Impaired in Patients With Spontaneous Carotid Dissection

Abstract: Background and Purpose-We undertook this case-control study in patients with unilateral spontaneous dissection of the cervical internal carotid artery to investigate spontaneous and endothelium-independent dilation of the nondissected, contralateral carotid arteries and the ipsilateral brachial artery using high-resolution ultrasound. Methods-Spontaneous and endothelial-independent (nitroglycerin-mediated) absolute and relative dilation were assessed in the internal and common carotid and brachial arteries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The increase of carotid sinus length during the first 45°of head rotation was 90% in controls but only 60% in patients. This difference is in accordance with the findings of case-control studies that have shown that carotid artery dilation is reduced in patients with sICAD (3,6). The lack of significance between the two groups in the present study (P Ͼ 0.48) may be related to the low number of the 10 investigated subjects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase of carotid sinus length during the first 45°of head rotation was 90% in controls but only 60% in patients. This difference is in accordance with the findings of case-control studies that have shown that carotid artery dilation is reduced in patients with sICAD (3,6). The lack of significance between the two groups in the present study (P Ͼ 0.48) may be related to the low number of the 10 investigated subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with sICAD have a higher prevalence of hereditary connective tissue disorders such as Marfan syndrome, Ehlers Danlos syndrome, osteogenesis imperfecta, and, in particular, fibromuscular dysplasia (2,16,17,31,35,(37)(38)(39). In addition, several case-control studies have shown that vasomotion is impaired in patients with sICAD (3,6). Despite this, we have assumed constant material properties along the carotid arteries of patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In addition, both endothelium-dependent and endotheliumindependent vasodilatation was found to be impaired in patients with SD. 17,18 Several studies have failed to demonstrate any association between various connective tissue disorder genes and SD, and there is some evidence that the apolipoprotein E (e4 allele), which is associated with to premature atherosclerosis, may further protect against SD. 9,19 Spontaneous dissections have been linked to a proinflammatory predisposition with polymorphism of the intercellular adhesion molecule 1 with a 3-fold increased risk of SD, indicating a possible role for an abnormal inflammatory response.…”
Section: Inherited and Genetic Risksmentioning
confidence: 99%
“…[47][48][49][50] During conventional angiography, between 12% and 18% of patients with carotid dissections are found to have changes consistent with fibromuscular dysplasia. [53][54][55][56] Heritable connective tissue disorders have been associated with an increased risk of spontaneous dissection. [53][54][55][56] Heritable connective tissue disorders have been associated with an increased risk of spontaneous dissection.…”
Section: Intrinsic Factorsmentioning
confidence: 99%